2009
DOI: 10.2478/s11532-009-0092-1
|View full text |Cite
|
Sign up to set email alerts
|

Atom transfer radical polymerization in aqueous dispersed media

Abstract: During the last decade, atom transfer radical polymerization (ATRP) received significant attention due to its exceptional capability of synthesizing polymers with pre-determined molecular weight, well-defined molecular architectures and various functionalities. It is economically and environmentally attractive to adopt ATRP to aqueous dispersed media, although the process is challenging. This review summarizes recent developments of conducting ATRP in aqueous dispersed media. The issues related to retaining "c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
105
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(101 citation statements)
references
References 138 publications
0
105
0
Order By: Relevance
“…Graftingthrough or macromonomer technique is a simpler approach for the synthesis of graft copolymers that can control number of side chains. 17,18 Emulsion ATRP was initially attempted in 1998 by Krzysztof Matyjaszewski, 19 whose work focused on successful preparation of well-defined polymers for n-butyl acrylate, methyl methacrylate, n-butyl methacrylate, and styrene as calculated by low PDIs and molecular weights in agreement with predicted values. Schulze 12 reported that PS macromonomers were prepared by ATRP in toluene.…”
Section: Introductionmentioning
confidence: 99%
“…Graftingthrough or macromonomer technique is a simpler approach for the synthesis of graft copolymers that can control number of side chains. 17,18 Emulsion ATRP was initially attempted in 1998 by Krzysztof Matyjaszewski, 19 whose work focused on successful preparation of well-defined polymers for n-butyl acrylate, methyl methacrylate, n-butyl methacrylate, and styrene as calculated by low PDIs and molecular weights in agreement with predicted values. Schulze 12 reported that PS macromonomers were prepared by ATRP in toluene.…”
Section: Introductionmentioning
confidence: 99%
“…Besides assuring colloidal stability of the latex particles, the surfactant also plays an important role in retaining the catalyst complex in the oil phase, as the reaction takes place in the monomers droplets. A good surfactant for a controlled ATRP in emulsion should at least meet the following criteria11: (i) provide a stable dispersed system throughout the polymerization and (ii) do not interfere with the equilibrium between the radicals and the dormant species.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, as its adaptability to most monomers and commercially available initiators, it has emerged as one of the most powerful synthetic techniques for preparation of well‐defined polymeric material 9. ATRP can be widely conducted in solution, bulk,10 dispersion,11 and emulsion12 polymerization systems. Last decade has witnessed the great progress including new initiation‐catalyst systems,13, 14new monomers,15 and new routes16 in conducting ATRP.…”
Section: Introductionmentioning
confidence: 99%
“…It is an attractive medium for exothermic radical copolymerization reactions, particularly since both solution polymerization of water‐soluble monomers and biphasic polymerization of hydrophobic monomers in latexes have found direct industrial scale applications in various practical fields. It is possible to prepare polymer latexes and solid particles over a wide range of size, nm to mm, by employing the full spectrum of aqueous dispersed media: suspension, dispersion, emulsion, miniemulsion, microemulsion and inverse miniemulsion systems 40. One advantage of biphasic media for the preparation of polymers from initiators containing multiple initiation sites is that there is a further segregation of the low concentration of active radicals through compartmentalization41 which reduces the formation of macroscopic crosslinked gels.…”
Section: Atrp In Aqueous Systemsmentioning
confidence: 99%